2019
DOI: 10.1007/s00198-019-05241-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk for hip fracture before and after total knee replacement in Sweden

Abstract: We studied the risk for hip fracture before and after total knee replacement (TKR) in the entire population in Sweden. Women and men had a low risk for hip fracture before TKR but an increased risk the first year after TKR. Purpose It is known that osteoarthritis is associated with high bone mass. We therefore studied the risk of hip fracture before and after total knee replacement (TKR), risk of different hip fracture types, and risk subdivided in genders and age groups. Methods We followed the total Swedish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Partial hip replacements are the main operation procedure were using for it and shows in 45.1%. Compared with a study done it in Sweden [15], the hip replacements were the fundamental procedure which is using for it especially among elderly. The main causes of hip fractures was tumbling and fall from the height and shows in 38.5% compared with other study in New Zealand (10), they reported the majority were fall and exposed to traffic accident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial hip replacements are the main operation procedure were using for it and shows in 45.1%. Compared with a study done it in Sweden [15], the hip replacements were the fundamental procedure which is using for it especially among elderly. The main causes of hip fractures was tumbling and fall from the height and shows in 38.5% compared with other study in New Zealand (10), they reported the majority were fall and exposed to traffic accident.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of fracture recurrence persists in ten years, which illustrates the importance of treating primary fractures quickly and effectively [14]. Treatment options include surgery, and statistics indicated that more than three-quarters of people with a broken hip undergo surgery, often a joint replacement [15]. Surgical intervention usually occurs to 48 hours [16].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis can increase the risk of periprosthetic fracture. Studies have also shown an increased risk of hip fracture 1 to 5 years after THA and TKA [32,39]. Studies looking at periprosthetic fracture during TKA have shown an incidence of 0.3% to 2.5% [9,33].…”
Section: Complicationsmentioning
confidence: 99%
“…OA ve kalça kırığı benzer popülasyonları etkileyebilmesine ve karşılaştırılabilir fonksiyonel bozukluklara neden olabilmesine rağmen, yapılan çalışmalarda kalça kırığı olan hastalarda osteoartritin daha az olduğunu göstermektedir. [22][23][24] Bununla birlikte, OA kalça kırığı riskini artırabilecek veya azaltabilecek bir dizi faktörle ilişkili olduğundan, bu iddianın geçerliliği belirsizdir. [24] Örneğin, bir kalça kırığı oluşma riski, belirli bir yaş kategorisinde daha düşük kemik mineral yoğunluğuna sahip olanlar arasında daha yüksektir.…”
Section: Kalça Kiriği İle Kalça Osteoartri̇ti̇ Arasindaki̇ İli̇şki̇unclassified